Strategi Guru Dalam Meningkatkan Keterampilan Membaca Alquran Siswa Di SDIT Aulia Batanghari - Ahmad Hariandi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2019)
The purpose of this study is to describe the Teacher's Strategy in Improving Reading Skills for Al-Qur'an Students at SDIT Aulia Batanghari. Qualitative descriptive research type. The results of the teacher's strategy in improving Al-Qur'an reading skills are the application of the Qur'anic learning method in the classroom, mentoring, teacher cooperation with peers, cooperation with schools with parents, school collaboration with the community and the provision of facilities and infrastructure. The factors that support the PAI teacher's strategy in improving Al-Qur'an reading skills include: Students already have the ability to read the Qur'an, a family environment that can be a role model and teach children to read the Qur'an. PAI teachers are competent and are committed to improving Al-Qur'an reading skills to their students. Islamic community environment. Facilities and infrastructure in schools are adequate.